2022
DOI: 10.4240/wjgs.v14.i7.706
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous aspiration and sclerotherapy of a giant simple hepatic cyst causing obstructive jaundice: A case report and review of literature

Abstract: BACKGROUND Giant simple hepatic cysts causing intrahepatic duct dilatation and obstructive jaundice are uncommon. A variety of measures with different clinical efficacies and invasiveness have been developed. Nonsurgical management, such as percutaneous aspiration and sclerotherapy, is often applied. CASE SUMMARY The case is a 39-year-old female with a 5-mo history of cutaneous and scleral icterus, loss of appetite, and dark urine. Lab tests showed jaundice and liver fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 39 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Hepatic simple cysts typically manifest asymptomatically and are commonly discovered incidentally via abdominal imaging modalities [ 1 , 6 ]. Simple cysts may present as solitary or multiple lesions, varying in size from millimeters to exceeding than 20 cm in diameter [ 2 , 4 , 7 ]. While symptoms are infrequent, complications may arise due to intracystic bleeding, rupture, or secondary bacterial infection [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hepatic simple cysts typically manifest asymptomatically and are commonly discovered incidentally via abdominal imaging modalities [ 1 , 6 ]. Simple cysts may present as solitary or multiple lesions, varying in size from millimeters to exceeding than 20 cm in diameter [ 2 , 4 , 7 ]. While symptoms are infrequent, complications may arise due to intracystic bleeding, rupture, or secondary bacterial infection [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simple cysts may present as solitary or multiple lesions, varying in size from millimeters to exceeding than 20 cm in diameter [ 2 , 4 , 7 ]. While symptoms are infrequent, complications may arise due to intracystic bleeding, rupture, or secondary bacterial infection [ 2 , 6 ]. Compression of neighboring structures may ensue, such as compression of the inferior vena cava leading to lower extremity edema, compression of the portal vein culminating in portal hypertension, or compression of the biliary tree leading to cholestasis [ 1 , 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He et al presented the challenges of managing giant simple liver cysts accompanied by obstructive jaundice and compared the safety and efficacy of percutaneous aspiration and lauromacrogol sclerotherapy with other management strategies. 14 The case is a 39-year-old woman with jaundice and abnormal liver function. Imaging studies revealed a giant simple liver cyst with obstruction of the intrahepatic bile ducts.…”
Section: Discussionmentioning
confidence: 99%